River Confluence Model: flow depth estimator (RICOMOD) / Nor Azni Shahari, Nor Arif Husaini Norwaza and Iskandar Shah Mohd Zawawi - Shahari, Nor Azni; Norwaza, Nor Arif Husaini; Mohd Zawawi, Iskandar Shah (UiTM Cawangan Negeri Sembilan, 2021)
The overflow of water in the river is mainly caused by the heavy rain and inefficient structure of the drainage system especially at its channel junction will make it become worse. At the junction when two rivers combine is defined as river confluence. In this confluence mixing of flow from upstream and lateral stream happens and if the depth of the downstream cannot hold a certain amount of water, this can damage the riverbank and flood can happen. To avoid overflow of water after the confluence junction, it is necessary to predict the maximum depth at the channel before the junction. When this phenomenon happens, field measurement incurs higher cost and time consuming. Therefore, a mathematical model, that is cheaper and simpler, would be an alternative approach for flood mitigation. This derived model, namely RICOMOD, is implemented by MATLAB software to provide a user- friendly tool for the results analysis. This model could assist the Department of Irrigation and Drainage (JPS) in its decision making regarding the suitable depth ratio to avoid flooding rivers, computing the amount of river flow rates, and validating the results achieved by the experiment methods.